Imaging God: A Theological Answer to the Anthropological Question? - McFadyen, Alistair I. (Zygon, 2012)
Traditionally the central trope in Christian theological anthropology, “the image of God” tends to function more as a noun than a verb. While that has grounded significant interplay between specific Christian formulations and the concepts of nontheological disciplines and cultural constructs, it facilitates the withdrawal of the image and of theological anthropology more broadly from the context of active relation with God. Rather than a static rendering of the image a more interactionist, dynamic, and relational view of “imaging God” is commended as a key anthropological term. Engaging with Psalm 8 suggests that, biblically, asking the anthropological question “What is humanity?” is tied to the answer to the theological question: who is God? This locates theological anthropology securely within the interactive context of being related to by God and suggests that theological anthropology might be a matter of performance rather than definition: actively imaging God.